2010
DOI: 10.5433/1679-0359.2010v31n2p289
|View full text |Cite
|
Sign up to set email alerts
|

Influência de folhas e lesões na base de estacas herbáceas no enraizamento de goiabeira da seleção 8501-9

Abstract: ResumoCom o objetivo de avaliar o potencial de enraizamento da seleção 8501-9 de goiabeira utilizou-se estacas herbáceas com 10-12 cm de comprimento em duas formas de preparo (corte simples sem lesão e exposição do câmbio) e três intensidades de supressão das folhas (sem folhas, com folhas cortadas ao meio e folhas intactas). O delineamento experimental foi inteiramente casualizado com cinco repetições em arranjo fatorial 2 x 3, com dez estacas por parcela. Após tratamento com AIB as estacas foram colocadas pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 2 publications
0
14
0
8
Order By: Relevance
“…This was also observed for "jabuticaba" (SASSO et al, 2010), guava (SANTORO et al, 2010) and pineapple guava (FRANZON et al, 2004).…”
Section: Ornamental Horticulturementioning
confidence: 63%
See 2 more Smart Citations
“…This was also observed for "jabuticaba" (SASSO et al, 2010), guava (SANTORO et al, 2010) and pineapple guava (FRANZON et al, 2004).…”
Section: Ornamental Horticulturementioning
confidence: 63%
“…However, when considering only the influence of presence of leaves, it was found that the conservation of leaves is essential to the survival of the cuttings. However, the conservation of a pair of full or cut in half leaves did not differ regarding the percentage of rooted cuttings, number of roots, length and survival of cuttings, differing only in root fresh and dry matter, which was higher in cuttings with full leaves (SANTORO et al, 2010). Similar results were observed in this study, where the presence of leaves was effective to the survival and rooting of cuttings, showing a negative correlation (-0.71) between leaf retention and cutting mortality (Figure 2).…”
Section: Ornamental Horticulturementioning
confidence: 80%
See 1 more Smart Citation
“…It is possible to verify a higher root biomass, variable that demonstrates the vigor of the roots (Paulus et al, 2014) The superior results for shoot/sprout diameter in cuttings with only two leaves can be explained by the stimulus that is given to the cutting for the production of photosynthetically active structures after the leaves removal (Santoro et al, 2010).…”
Section: Experiments IImentioning
confidence: 99%
“…No entanto, estas variáveis apresentaram valores inferiores para as estacas com ausência de folhas, sendo 90% menores em relação à matéria fresca e comprimento de raízes. SANTORO et al (2010) observaram que a presença de folhas inteiras promove maior massa fresca e seca das raízes das estacas, sendo fundamentais para a promoção do enraizamento em goiabeira. LIMA et al (2006), estudando tamanhos de estacas verificaram que estacas de 10 cm de comprimento retiradas da porção mediana dos ramos são apropriadas para a produção de mudas de aceroleira por estaquia, em condições de casa de vegetação com nebulização intermitente.…”
Section: Production Golden Dew Drop Seedlings From Different Sizes Ofunclassified